Evaluating exercise training effectiveness for preventing musculoskeletal injuries through systematic review - Wahyudin, Amirul; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Adnan, Aizzat; Linoby, Adam; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This systematic review and meta-analysis evaluates the efficacy of exercise-based interventions in preventing musculoskeletal injuries among healthy adolescents and adults. By synthesizing randomized controlled trials from major databases through January 2025, the research utilizes a random-effects model to calculate pooled risk ratios across various modalities, including strength, proprioception, and multicomponent training. The study addresses fragmentation in current literature by conducting stratified analyses on injury types and age groups, aiming to provide a definitive assessment of how structured exercise protocols mitigate injury incidence in sports and physical activity.